Effective downsizing but enhanced intratumoral heterogeneity following neoadjuvant sorafenib in patients with non-metastatic renal cell carcinoma - Hatiboglu, Gencay; Hohenfellner, Markus; Arslan, Aysenur; Hadaschik, Boris; Teber, Dogu; Radtke, Jan Philipp; Hallscheidt, Peter; Tolstov, Yanis; Roth, Wilfried; Grüllich, Carsten; Hüsing, Johannes; Duensing, Stefan; et al. (Langenbeck's archives of surgery, 2017)
Objectives To evaluate the safety and feasibility of sorafenib prior to surgery for downsizing tumors in patients with nonmetastatic cT1-3 renal tumors together with a characterization of functional intratumoral heterogeneity (ITH).